1998
DOI: 10.1038/sj.bjc.6690002
|View full text |Cite
|
Sign up to set email alerts
|

Borderline ovarian tumours in Vaud, Switzerland: incidence, survival and second neoplasms

Abstract: Summary Between 1976 and 1996, 176 borderline ovarian tumours were registered in the Cancer Registry of the Swiss canton of Vaud, corresponding to an age-adjusted incidence (world standard) of 2.7 in 100 000. Incidence rose from 1.7 per 100 000 during 1976-81 to 2.7 per 100 000 during 1987-91, and then levelled off; 58% of cases were serous and 41% mucinous. Relative survival was 94% at 10 years; 18 second neoplasms were observed, compared with 10.3 expected, and there was a significant excess of invasive ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 25 publications
5
19
0
1
Order By: Relevance
“…In Israel stieg die Inzidenz von 0,83 in den Jahren 1985-89 auf 1,54 pro 100 000 Frauen in den Jahren 1990-1993 [90]. Eine Zunahme der Inzidenz von 1,7 auf 2, 7 von 1976-1981, verglichen mit 1987-1991, wird auch für die Schweiz berichtet [91]. In Schweden stieg die Inzidenz seit 1960 von 1,0 auf 5,3 im Jahr 2005 an, während die Inzidenz der invasiven Karzinome seit 2000 etwas abgefallen ist; daraus ergibt sich ein Anstieg des Anteils der BOT an den Ovarialmalignomen von 5-10 % in den 60er-und 70er-Jahren auf 25 % seit 1995 [89].…”
Section: Einleitung Epidemiologie Und Risikofaktorenunclassified
“…In Israel stieg die Inzidenz von 0,83 in den Jahren 1985-89 auf 1,54 pro 100 000 Frauen in den Jahren 1990-1993 [90]. Eine Zunahme der Inzidenz von 1,7 auf 2, 7 von 1976-1981, verglichen mit 1987-1991, wird auch für die Schweiz berichtet [91]. In Schweden stieg die Inzidenz seit 1960 von 1,0 auf 5,3 im Jahr 2005 an, während die Inzidenz der invasiven Karzinome seit 2000 etwas abgefallen ist; daraus ergibt sich ein Anstieg des Anteils der BOT an den Ovarialmalignomen von 5-10 % in den 60er-und 70er-Jahren auf 25 % seit 1995 [89].…”
Section: Einleitung Epidemiologie Und Risikofaktorenunclassified
“…Data are scanty on second cancers after borderline ovarian cancers, but some excess has been reported for ovarian (Levi et al, 1999), colorectal and breast cancers (Casey et al, 1993;Bouchardy et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Esophageal carcinoma was reported in only 5 of 1296 second primary malignancies; however, whether it was squamous cell carcinoma or adenocarcinoma was not defined. Moreover, in another three studies, from the National Cancer Institute of Canada, the Cancer Registry of the Canton of Vaud, and the Birmingham study, among a total of 1859 women with ovarian cancer, 194 second primary malignancies were diagnosed and only 1 proved to be an esophageal carcinoma [3,5,8].…”
Section: Discussionmentioning
confidence: 98%
“…During the last years, a number of population-based studies focusing on second primary malignancies after an ovarian cancer have been reported [3][4][5][6][7][8]. All of them concluded that as the life expectancy of ovarian cancer patients has been extended over the last two decades because of improved therapeutic modalities, second primary tumors are being diagnosed more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation